2015
DOI: 10.1016/j.biosystems.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Navigation-specific neural coding in the visual system of Drosophila

Abstract: Please cite this article in press as: Dewar, A.D.M., et al., Navigation-specific neural coding in the visual system of Drosophila. BioSystems (2015), http://dx.doi.org/10.1016/j.biosystems.2015.07.008 Drosophila melanogaster are a good system in which to understand the minimal requirements for widespread visually guided behaviours such as navigation, due to their small brains (adults possess only 100,000 neurons) and the availability of neurogenetic techniques which allow the identification of task-specific ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…This problem has been approached from the other direction, i.e. from known properties of insect visual receptive fields to navigational behaviour [82][83][84]. This work uses the receptive fields described in [80], or a generalized version of them, to encode omnidirectional views for an insect navigation task.…”
Section: Discussionmentioning
confidence: 99%
“…This problem has been approached from the other direction, i.e. from known properties of insect visual receptive fields to navigational behaviour [82][83][84]. This work uses the receptive fields described in [80], or a generalized version of them, to encode omnidirectional views for an insect navigation task.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the BU-EB neurons have not been systematically characterized, available information regarding these neurons was used to hypothesize the arborization structure for a total of 80 BU-EB neurons in each hemisphere of the fly brain (Hanesch et al, 1989; Young and Armstrong, 2010b; Seelig and Jayaraman, 2013; Dewar et al, 2015). Likewise, we also hypothesized isomorphic sets of pontine neurons that link regions in FB based upon (Hanesch et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…EB appears to be involved in visual place learning (Ofstad et al, 2011; Dewar et al, 2015), short-term orientation memory (Neuser et al, 2008; Seelig and Jayaraman, 2013; Wystrach et al, 2014), angular path integration (Seelig and Jayaraman, 2015), and left-right bargaining (Strauss, 2014);…”
Section: Introductionmentioning
confidence: 99%
“…They achieve this task by using retinotopic imagematching methods, which has inspired a range of bio-inspired algorithms (Ants: [6][7][8]; Bees: [3]; Review: [9]). We have previously shown that panoramic images can be used for navigation in desert ant-inspired algorithms even if images are low-resolution [10], processed through coarse visual filters modelled on parts of the drosophila visual system [11], or processed so that only the height of objects against the skyline is used [12]. This work not only demonstrates the robustness of using low-resolution images for navigation but also that they can be better than high-resolution images [10].…”
Section: Introductionmentioning
confidence: 82%